Portfolio diversification benefits of alternative currency investment in Bitcoin and foreign exchange markets - Muhammad Owais Qarni; Saiqb Gulzar (Financial Innovation, 2021)
This study examines the portfolio diversification benefits of alternative currency trading in Bitcoin and foreign exchange markets. The following methods are applied for the analysis: the spillover index method of Diebold and Yilmaz (Int J Forecast 28(1): 57-66, 2012. https://doi.org/10.1016/j.ijforecast.2011.02.006), the spillover asymmetry measures of Barunik et al. (J Int Money Finance 77: 39-56, 2017. https://doi.org/10.1016/j.jimonfin.2017.06.003), and the frequency connectedness method of Barunik and Kérehlík (J Financ Econom 16(2): 271-296, 2018. https://doi.org/10.1093/jjfinec/nby001). The findings identify the presence of low-level integration and asymmetric volatility spillover as well as a dominant role of short horizon spillover among Bitcoin markets and foreign exchange pairs for six major trading currencies (US dollar, euro, Japanese yen, British pound sterling, Australian dollar, and Canadian dollar). Bitcoin is found to provide significant portfolio diversification benefits for alternative currency foreign exchange portfolios. Alternative currency Bitcoin trading in euro is found to provide the most significant portfolio diversification benefits for foreign exchange portfolios consisting of major trading currencies. The findings of the study regarding spillover dynamics and portfolio diversification capabilities of the Bitcoin market for foreign exchange markets of major trading currencies have significant implications for portfolio diversification and risk minimization.
Keywords: G10; G15; G19; 650; Bitcoin; Frequency connectedness; Major trading currencies; Spillover asymmetry measure; Spillover index